The Influence of Local Own Source Revenue, Fiscal Balance Transfer and Regional Budget Expenditure on Sustainable Development Goals (SDGs) Social Aspects in Palangka Raya City - Haga, Ronni (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
This study examines the impact of Regional Revenue Local Own Source Revenue and Balancing Funds on the achievement of Sustainable Development Goals (SDGs) in social aspects in Palangka Raya City, mediated by Regional Expenditure. Utilizing secondary data from 2010 to 2022, the study employs path analysis to explore the relationships between Regional Original Revenue Local Own Source Revenue, Regional Expenditure, and SDGs. The results indicate that Local Own Source Revenuehas a positive but non-significant influence on Regional Expenditure, whereas Balancing Funds show a significant positive impact on Regional Expenditure. In the context of social SDGs, Local Own Source Revenue demonstrates a significant positive effect, but the impact of Balancing Funds on social SDGs is not significant. Furthermore, both Local Own Source Revenue and Balancing Funds, when mediated by Regional Expenditure, exhibit a negative and non-significant effect on social SDGs. These findings underline the challenges of using fiscal levers to achieve social development goals within the framework of fiscal decentralization.